Mechanism Analysis and Experimental Study on Friction Noise of Vehicle V-ribbed Belt - Wusheng Tang; Kai Ning; Yaochen Shi; Xuelian Yu (Jixie chuandong)
In order to study the characteristics and variation of noise in vehicle V-ribbed belt transmission， the mechanism of V-ribbed belt noise is analyzed. By establishing the theoretical model of friction vibration， the unstable conditions of V-ribbed belt transmission system are deduced. The vibration and noise of V-ribbed belt transmission are measured on the designed vibration and noise test bench. The experimental results show that，the fluctuation of tension force results in low frequency vibration noise of V-ribbed belt， and the viscoelastic sliding between belt and pulley results in high frequency friction noise.